From 'Big 4' to 'Big 5': a review and epidemiological study on the relationship between psychiatric disorders and World Health Organization preventable diseases. Issue 5 (September 2016) - Chartier, Gabrielle; Cawthorpe, David
Abstract : Purpose of review: This study outlines the rationale and provides evidence in support of including psychiatric disorders in the World Health Organization's classification of preventable diseases. The methods used represent a novel approach to describe clinical pathways, highlighting the importance of considering the full range of comorbid disorders within an integrated population-based data repository. Recent findings: Review of literature focused on comorbidity in relation to the four preventable diseases identified by the World Health Organization. This revealed that only 29 publications over the last 5 years focus on populations and tend only to consider one or two comorbid disorders simultaneously in regard to any main preventable disease class. Summary: This article draws attention to the importance of physical and psychiatric comorbidity and illustrates the complexity related to describing clinical pathways in terms of understanding the etiological and prognostic clinical profile for patients. Developing a consistent and standardized approach to describe these features of disease has the potential to dramatically shift the format of both clinical practice and medical education when taking into account the complex relationships between and among diseases, such as psychiatric and physical disease, that, hitherto, have been largely unrelated in research.